Trends and Challenges in Gamification for Elementary Education A Bibliometric and Systematic Literature Review - Pangestu, Aditya; Aminah, Aminah; Wulandari, Ghina Antania; Noto, Muchamad Subali; Tarmidzi, Tarmidzi (Publikasi Pendidikan, 2025)
This study aims to explore the use of gamification in elementary education and its influence on students’ learning experiences. Gamification, which involves incorporating game like elements into instructional practices, has emerged as an innovative strategy to boost student engagement and motivation. Adopting a bibliometric and systematic review approach, this study analyzed 188 articles retrieved from the Scopus database, focusing on publications addressing gamification in elementary education between 2013 and 2024. Results indicate a marked rise in research outpour starting around 2014, reflecting growing academic interest in this field. The findings reveal that well-designed gamification can enhance student motivation, participation, and learning outcomes. Nonetheless, several barriers were identified, including limited resources, insufficient teacher training, and challenges in aligning game based approaches with existing curricula. The study also suggests that combining gamification with active and interactive teaching methods yields better results compared to traditional approaches. Based on these insights, it recommend that schools and policymakers strengthen their support for developing and implementing gamification strategies in elementary education and invest in ongoing teacher professional development. By addressing these challenges, gamification can serve as a valuable tool for improving the quality of elementary education in Indonesia.